2000
DOI: 10.1002/1522-2683(20000701)21:12<2531::aid-elps2531>3.3.co;2-5
|View full text |Cite
|
Sign up to set email alerts
|

Two-dimensional electrophresis and mass spectrometry identification of proteins bound by a murine monoclonal anti-cardiolipin antibody: A powerful technique to characterize the cross-reactivity of a single autoantibody

Abstract: Antigenic cross-reactivity, i.e., the capacity of a single antibody to react with apparently dissimilar structures, is a common characteristic of autoantibodies produced during systemic lupus erythematosus (SLE), an autoimmune disease developed by humans and certain strains of mice. Characterization of the extent of cross-reactivity of SLE-related autoantibodies may help identify the immunogenic stimulus, or stimuli, of autoantibody-secreting B-lymphocytes. Two-dimensional polyacrylamide gel electrophoresis (2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2002
2002
2005
2005

Publication Types

Select...
4

Relationship

4
0

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 0 publications
0
8
0
1
Order By: Relevance
“…Similarly, antinucleophosmin autoantibodies were previously detected in SLE patients, and were shown to be constantly associated with the presence of anti-CL Abs (23). It is worth noting that two monoclonal autoantibodies, one derived from the PBL of an SLE patient, and the other from male WB splenocytes, and both selected based on their capacities to react with anionic phospholipids, also bound to vimentin (24) and nucleophosmin (19), respectively. These observations, and the high frequency of anti-vimentin and anti-FIGURE 7.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, antinucleophosmin autoantibodies were previously detected in SLE patients, and were shown to be constantly associated with the presence of anti-CL Abs (23). It is worth noting that two monoclonal autoantibodies, one derived from the PBL of an SLE patient, and the other from male WB splenocytes, and both selected based on their capacities to react with anionic phospholipids, also bound to vimentin (24) and nucleophosmin (19), respectively. These observations, and the high frequency of anti-vimentin and anti-FIGURE 7.…”
Section: Discussionmentioning
confidence: 99%
“…All reagents and instruments used have been described in detail elsewhere (19). Protein sample preparation.…”
Section: D-page Map Constructionmentioning
confidence: 99%
“…The immunofluorescence pattern of sera from WB mice and patients with SLE was determined on Hep-2 cells as described previously [ 10 ]. Inhibition experiments were performed by preincubating an anti-NPM mouse mAb (Invitrogen immunodetection, San Francisco, CA, USA), mouse and patient sera for 1 hour with 20 μg of recombinant NPM.…”
Section: Methodsmentioning
confidence: 99%
“…We previously observed that WB mouse-derived monoclonal antibodies (mAbs) selected for their capacities to react with CL in the presence of FCS also reacted with nuclear antigens, as shown by their nucleolar immunofluorescence-labelling pattern on HEp-2 cells [ 10 ]. One of these mAbs, 4B7, reacted with nucleophosmin (NPM; also known as B23), a nucleolar protein involved in the assembly and transport of ribosomes [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Cela constitue le principal avantage et l'originalité de cette technologie, largement utilisée pour l'exploration du répertoire des auto-anticorps dans diverses pathologies et pour l'analyse des processus physiopathologiques à l'oeuvre dans les maladies auto-immunes [19][20][21][22][23]. Son principal inconvénient réside dans la lourdeur de sa mise oeuvre et de sa standardisation.…”
Section: Revuesunclassified